Carrying Capacity Assesment Based on Chlorophyll-a in The Perupuk Lake, Kampung Pinang Village, Kampar District, Perhentian Raja Subdistric, Riau Province for Extensive Fishing - Efredy Tamba; Asmika Harnalin Simarmata; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTCarrying capacity is defined as the ability of aquatic environment to support the life organism in that area. This study aimed to assess the aquatic carrying capacity of the Perupuk Lake for extensive fishing. The carrying capacity was determined based on primary productivity using the chlorophyll concentration, which is indicating the existence of phytoplankton in waters. A study was conducted in June-July 2019 in Perupuk Lake. There were 3 stations, namely station 1 (inlet area), station 2 (in the middle of  lake) and station 3 (the end of the lake). In each station, there were 2 sampling points, in the surface (0.15 m) and 2 Secchi (0.90 m). Sampling were conducted 3 times, once/week. Water quality parameters measured were transparency, temperature, pH, dissolved oxygen, CO2, nitrate, phosphate, and chlorophyll-a concentration. Results shown water quality parameters were as follows: concentration of chlorophyll-a was 7.32-8.65 µg/L, transparency 45-50 cm, temperature 28-30oC, pH 5, dissolved oxygen 5.35-6.4 mg/L, CO2  7.32-14.64mg/L, phosphate 0.03-0.06 mg/L, and nitrate 0.12-0.0.18 mg/L. Based on chlorophyll-a concentration, carrying capacity of the Perupuk Lake for extensive fishing was 0.906 tons/year.Keywords :Oxbow lake, primary productivity,phytoplankton, water quality, aquatic